Consumer Decisions in Purchasing Consumed Fish at PPI Lonrae, Bone Regency - Muhtar, Dian Islamia; Wahid, Abdul; Tahang, Hamzah; Made, Sutinah; Hasani, M. Chasyim (Program Studi Sosial Ekonomi Perikanan, Fakultas Ilmu Kelautan dan Perikanan, Universitas Hasanuddin, 2022)
This study aims to analyze the variable factors that influence consumer decisions and the dominant factors influencing the purchase of consumption fish at PPI Lonrae, Bone Regency. The research was carried out in December 2021 in Bone Regency. Determination of respondents using Accidental Sampling technique with a total sample of 96 respondents. Sources of data used are primary data and secondary data and then analyzed using multiple linear regression analysis, coefficient of determination, t test and F test. From the results of the study it was found that prices, tastes and consumer income affect consumer purchasing decisions in choosing consumption fish at PPI Lonrae. The result of the coefficient of determination is 0.985, which means that 98.5% of consumption fish purchasing decisions are influenced by the variables Price (X1), Taste (X2), Fish Quality (X3) and Consumer Income (X4). While the remaining 1.5% is influenced by other factors that are not included in the regression model but can also influence respondents in purchasing decisions for consumption fish. The results of the F test show that the variables of price, taste, fish quality and consumer income together have a significant effect on purchasing decisions. The results of the t-test indicate that the variables of price, taste, and consumer income partially have a significant effect on purchasing decisions.